STUDENT LEARNING EXPERIENCE THROUGH MICROSOFT TEAMS DURING THE PANDEMIC ERA - Mardhiyyah, Ana; Sulistyani, Sulistyani; Wicaksono, Agung; Khoiriyah, Khoiriyah (Premise: Journal of English Education and Applied Linguistics, 2022)
Students learning experiences are affected by the spread of Covid-19 in cognitive, affective, and behavioral domains. This research investigates the university students' experience using the Microsoft Teams application in online learning during the Covid-19 Pandemic. The experience includes their perception, problems, and how they use Microsoft Teams daily. It is descriptive quantitative research under a case study. The participants were 97 university students consisting of 50 female and 47 male students spread over various universities. The data collection techniques were questionnaires and five open-ended questions. The questionnaires were analyzed using the Likert scale through SPSS (Statistical Package for the Social Sciences), while five open-ended questions were analyzed using the content analysis technique. The results showed that the students had a good experience using Microsoft Teams. They also have much improvement in English skills, especially in speaking skills. However, they needed help using Microsoft Teams, had unstable internet connections, and found it hard to improve their reading skills. Nonetheless, students hope that this application will continue to be used during online learning with some improvements so that learning using this application can take place more effectively and efficiently. This study implies that Microsoft Teams can support English skill development in an online learning environment.